2019
DOI: 10.1002/slct.201901497
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@BNPs‐CPTMS‐Chitosan‐Pd(0) as an Efficient and Stable Heterogeneous Magnetic Nanocatalyst for the Chemoselective Oxidation of Alcohols and Homoselective Synthesis of 5‐Subestituted 1H‐Tetrazoles

Abstract: In this content, a stable, efficient, active, reusable and inexpensive magnetic boehmite was synthesized by hydrothermal sol-gel method. In the next step magnetic boehmite immobilized further with palladium chitosan complex (Fe 3 O 4 @BNPs-CPTMS-Chitosan-Pd (0)). This novel nanocatalyst was used for the oxidation of alcohols in ethanol and the preparation of 5-substituted tetrazoles in solvent-free conditions. To confirm the structure of catalyst, a variety of techniques, including FT-IR, XRD, FESEM, TEM, EDX,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…The Fe 3 O 4 @BNPs-CPTMS-chitosan-Pd(0) offered numerous advantages such as green ligand (Chitosan), thermal and mechanical stability, high-grade magnetic strength, high surface area, reusability (5 cycles), an easy and fast separation. 65 Akbarzadeh et al embedded chlorosulfonic acid functionalized carbon nanotubes on Fe 3 O 4 nanoparticles to produce 66 Similarly, it was found that, unmodied nano Fe 3 O 4 exhibited remarkable catalytic activity for 5-substituted tetrazole synthesis from malononitrile (1 mmol), aromatic aldehyde (1 mmol), sodium azide (1 mmol) as tabulated in Table 4, entry 4. They observed that nano Fe 3 O 4 gave best result at 20 mol% amount.…”
Section: Magnetic Nano-catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fe 3 O 4 @BNPs-CPTMS-chitosan-Pd(0) offered numerous advantages such as green ligand (Chitosan), thermal and mechanical stability, high-grade magnetic strength, high surface area, reusability (5 cycles), an easy and fast separation. 65 Akbarzadeh et al embedded chlorosulfonic acid functionalized carbon nanotubes on Fe 3 O 4 nanoparticles to produce 66 Similarly, it was found that, unmodied nano Fe 3 O 4 exhibited remarkable catalytic activity for 5-substituted tetrazole synthesis from malononitrile (1 mmol), aromatic aldehyde (1 mmol), sodium azide (1 mmol) as tabulated in Table 4, entry 4. They observed that nano Fe 3 O 4 gave best result at 20 mol% amount.…”
Section: Magnetic Nano-catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%
“…The Fe 3 O 4 @BNPs-CPTMS-chitosan-Pd(0) offered numerous advantages such as green ligand (Chitosan), thermal and mechanical stability, high-grade magnetic strength, high surface area, reusability (5 cycles), an easy and fast separation. 65 …”
Section: Magnetic Nano-catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%
“…This is in accordance with reported miller XRD. [55][56][57] The EDX analysis of the copper/Schiff base complex supported on amine-functionalized silica MMNPs is presented in Figure 4. Peaks for iron, oxygen, nitrogen, carbon, silica, and copper can be detected, confirming the presence of these elements in the structure of the nanoparticles.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Among different oxidation reactions, oxidation of benzyl alcohols into the corresponding benzaldehydes is a prominent chemical transformation in organic chemistry. [1][2][3][4][5] Aldehydes, which have various applications in different elds such as pharmaceuticals, dyes, perfumes, agriculture, food, beverages, agribusiness industries, and chemicals, are used as valuable oxygen-containing intermediates and raw materials in organic chemistry. In the past, despite numerous available methods for selective oxidation processes, most of them were not without drawbacks, generating a lot of by-products and pollutants.…”
Section: Introductionmentioning
confidence: 99%